Neuromolecular responses to social challenge: Common mechanisms across mouse, stickleback fish, and honey bee - Rittschof, Clare C.; Bukhari, Syed Abbas; Sloofman, Laura G.; Troy, Joseph M.; Caetano-Anollés, Derek; Cash-Ahmed, Amy; Kent, Molly; Lu, Xiaochen; Sanogo, Yibayiri O.; Weisner, Patricia A.; Zhang, Huimin; Bell, Alison M.; et al. (Proceedings of the National Academy of Sciences - PNAS, 2014)
Significance In some cases similar molecular programs (i.e., conserved genes and gene networks) underlie the expression of phenotypic traits that evolve repeatedly across diverse species. We investigated this possibility in the context of social behavioral response, using a comparative genomics approach for three distantly related species: house mouse ( Mus musculus ), stickleback fish ( Gasterosteus aculeatus ), and honey bee ( Apis mellifera ). An experience of territory intrusion modulated similar brain functional processes across species, including hormone-mediated signal transduction, neurodevelopment, chromosome organization, and energy metabolism. Several homologous transcription factors also responded consistently to territory intrusion, suggesting that shared neuronal effects may involve transcriptional cascades of evolutionarily conserved genes. These results indicate that conserved genetic “toolkits” are involved in independent evolutions of social behavior. Certain complex phenotypes appear repeatedly across diverse species due to processes of evolutionary conservation and convergence. In some contexts like developmental body patterning, there is increased appreciation that common molecular mechanisms underlie common phenotypes; these molecular mechanisms include highly conserved genes and networks that may be modified by lineage-specific mutations. However, the existence of deeply conserved mechanisms for social behaviors has not yet been demonstrated. We used a comparative genomics approach to determine whether shared neuromolecular mechanisms could underlie behavioral response to territory intrusion across species spanning a broad phylogenetic range: house mouse ( Mus musculus ), stickleback fish ( Gasterosteus aculeatus ), and honey bee ( Apis mellifera ). Territory intrusion modulated similar brain functional processes in each species, including those associated with hormone-mediated signal transduction and neurodevelopment. Changes in chromosome organization and energy metabolism appear to be core, conserved processes involved in the response to territory intrusion. We also found that several homologous transcription factors that are typically associated with neural development were modulated across all three species, suggesting that shared neuronal effects may involve transcriptional cascades of evolutionarily conserved genes. Furthermore, immunohistochemical analyses of a subset of these transcription factors in mouse again implicated modulation of energy metabolism in the behavioral response. These results provide support for conserved genetic “toolkits” that are used in independent evolutions of the response to social challenge in diverse taxa.